2017
DOI: 10.1177/0379572117700755
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Food Assistance in Northern Syria: An Evaluation of Transfer Programs in Idleb Governorate

Abstract: Continuation of multiple types of transfer programs, including both in-kind assistance and vouchers, will allow humanitarian actors to remain responsive to evolving access and security considerations, local needs, and market dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…, Alhaffar, Alawabdi et al 2019, Falb, Blackwell et al 2019, Roumieh, Bashour et al 2019), health seeking behaviours(Hamzeh, Almhanni et al 2019, Terkawi, Bakri et al 2019) and exposure to violence as a determinant of health(Vernier, Cramond et al 2019). Several other papers focus primarily on health determinants and risks, including neighbourhood socioeconomic status(Ahmad 2014, Ahmad, Fouad et al 2018, occupational stress(Othman, Steel et al 2018), food security(Doocy, Tappis et al 2017), and smoking prevalence and smoking behaviours before and during the war(Idris, Al Saadi et al 2018). Thirty-two research papers examine the various pillars of the health system.…”
mentioning
confidence: 99%
“…, Alhaffar, Alawabdi et al 2019, Falb, Blackwell et al 2019, Roumieh, Bashour et al 2019), health seeking behaviours(Hamzeh, Almhanni et al 2019, Terkawi, Bakri et al 2019) and exposure to violence as a determinant of health(Vernier, Cramond et al 2019). Several other papers focus primarily on health determinants and risks, including neighbourhood socioeconomic status(Ahmad 2014, Ahmad, Fouad et al 2018, occupational stress(Othman, Steel et al 2018), food security(Doocy, Tappis et al 2017), and smoking prevalence and smoking behaviours before and during the war(Idris, Al Saadi et al 2018). Thirty-two research papers examine the various pillars of the health system.…”
mentioning
confidence: 99%
“…resources Inadequate/irregular supplies of commodities 39 Logistical constraints 29 79 99 100 112 Limited human resources 83 89 Limited funding 42 Burundi, 48 Somalia, 39 Jordan, 41 51 79 95 Syria, 41 42 101 Sri Lanka, 49 Bosnia and Herzegovina, 54 77 Lebanon, 82 Lebanon, 91 South Sudan, 102 Yemen, 89 Afghanistan, 84 Syria, 101 Jordan, 41 80 DRC, 29 Uganda, 60 Colombia 94 Nutrition assessment, 29 84 101 102 breastfeeding and appropriate IYCF, 80 disease prevention and management, 29 micronutrient supplementation, 101 general food distribution, 29 Population movement 76 102 Gender bias or negative sociocultural practices 93 South Sudan, 102 Jordan, 80 92 Lebanon, 86 110 DRC, 76 102 Somalia, 93 Burundi, 76 Liberia, 76 Kenya, 63 Yemen 107 Nutrition assessment, 92 disease prevention and man...…”
Section: Insufficientmentioning
confidence: 99%
“…Unskilled staff 38 Reporting errors 62 73 Small sample size/Sampling bias 42 53 Security issues 42 Cameroon, 38 Kenya, 73 Pakistan, 62 Nigeria, 53 Syria, 42…”
Section: Poor Outcome Reportingmentioning
confidence: 99%
“…Cost-effectiveness analysis compares the relative costs of achieving desired social and/or economic results with different interventions. A recent study comparing in-kind food assistance, food voucher, and unrestricted voucher programs in Idlib governorate found that in-kind food assistance is more costly than alternative modalities but may still be the most costeffective strategy for achieving specific objectives or the only feasible option in some settings (Doocy et al 2015). These findings are consistent with global findings on cash-based approaches in humanitarian emergencies which concluded that how an intervention is designed and implemented plays a greater role in determining effectiveness than the emergency context or sector of implementation (Harvey and Bailey 2015).…”
Section: Value For Moneymentioning
confidence: 99%
“…Examples of cash-based interventions include both unconditional and multipurpose cash transfers, cash transfers with eligibility conditions (including cash for work), and vouchers that can be exchanged for specific items, services, or cash. When designed well, cash can be more effective, efficient, and acceptable to beneficiaries than in-kind assistance, though the efficiency of cash compared to in-kind assistance can vary significantly and depends on transportation and storage costs as well as local market prices (Doocy et al 2015;Harvey and Bailey 2015;Gairdner et al 2011).…”
Section: Introductionmentioning
confidence: 99%